Green Technology Accounting: Hospitality Industry Sustainability: Green Technology Accounting: Hospitality Industry Sustainability - Putri, Rumanintya Lisaria (Balitbangda Provinsi Jambi, 2024)
This study aims to determine the application of green technology in the hotel industry in Bali Province from an internal and external perspective. This type of research is a multi case study. Data collection was carried out in 2022, through interviews from internal parties at Grand Hyatt Bali (five stars), Sheraton Bali (four stars), and Aston Inn Hotel (three stars); guests and the surrounding community from the third hotel, the Bali Provincial Environmental Service; observations and documentation. The results of this study indicate that three, four and five star hotels in Bali Province have implemented several green technology accounting activities. The third hotel has also incurred some costs in order to reduce pollution and the environment. From the external side, no party feels disadvantaged from the hotel's operational activities,